PENINGKATAN KINERJA GURU DALAM MENERAPKAN MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARNING (CTL) MELALUI KEGIATAN SUPERVISI KLINIS - Abdul Wazir (Universitas Wijaya Kusuma Surabaya, 2022)
This study aims to determine the improvement of teacher performance in learning using the CTL learning model through clinical supervision at SMPN 1 Telen, Telen District, East Kutai Regency. carried out in 2 cycles with 2 meetings in each cycle. The research stages are planning, implementation, observation and reflection. The research subjects were class teachers at SMPN 1 Telen in the 2019/2020 academic year, totaling 10 people. Data collection techniques with observation and documentation activities. The data collection tool in this school action research activity uses 3 (three) assessment instruments, namely the Learning Implementation Plan Assessment (RPP), the Learning Planning Ability Assessment Instrument, and the Learning Implementation Ability Assessment Instrument, Evaluation, Follow-up. Data validation uses data and source triangulation. Data analysis used a qualitative descriptive technique. Based on data analysis, the results of the study indicate that the implementation of classroom supervision by the principal has proven to be successful in improving the performance of teachers for each subject at SMPN 1 Telen in managing the learning process by applying the contextual teaching and learning (CTL) learning model as evidenced by the increase in the results of observations carried out in 3 apeks. evaluation. In the aspect of the assessment of the Learning Implementation Plan (RPP) increased from 36.50 to 66.65 and 92.82 while the aspect of the assessment of the ability to plan learning increased from 53.62 to 77.66 and 88.61 and the aspect of the ability to carry out learning, evaluation, follow up continued from 54.24 to 75.73 and 84.47 at the end of the second cycle. Thus, it can be concluded that the implementation of clinical supervision has proven to be effective in improving the performance of SMPN 1 Telen teachers for the 2019/2020 academic year in implementing the contextual teaching and learning (CTL) learning model.